2017
DOI: 10.1177/0270467619861561
|View full text |Cite
|
Sign up to set email alerts
|

NGOs, Controversies, and “Opening Up” of Regulatory Governance of Science in India

Abstract: Nongovernmental organizations (NGOs) and scientific controversies are often the common denominators in most of the cases that have significantly shaped science and society relationships in the Global South during the past two decades. National and international NGOs and their network have often facilitated the “opening up” of regulatory governance in multiple sectors. This article draws from three cases—the bottled water controversy, the agribiotechnology debates, and the nanotechnology initiatives—and charts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…We found that the technical committee is dominated by bureaucrats and technocrats from ministries, public research institutes and big industries, unlike high-end regulations in developed countries, which are predominantly dominated by scientists and engineers from diverse fields (Jasanoff, 1990; Majone, 1984; Nowotny et al, 2001). The scientific controversy over pesticide residue in 2003 paved the way for the broader participation of different regulatory actors in the regulation-making process (JPC, 2004; Pandey & Sharma, 2017). After that, consumer organisations and NGOs were included as stakeholders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that the technical committee is dominated by bureaucrats and technocrats from ministries, public research institutes and big industries, unlike high-end regulations in developed countries, which are predominantly dominated by scientists and engineers from diverse fields (Jasanoff, 1990; Majone, 1984; Nowotny et al, 2001). The scientific controversy over pesticide residue in 2003 paved the way for the broader participation of different regulatory actors in the regulation-making process (JPC, 2004; Pandey & Sharma, 2017). After that, consumer organisations and NGOs were included as stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these products, such as drinking water, salt, sugar, cooking oil, flavour additives and the plastic used for packaging food items, are widely used and significantly shape everyday life. The safety and efficacy of such products are often debated in the public realm if controversies erupt (Bhaduri & Sharma, 2014; Lustig, et al, 2012; Pandey & Sharma, 2017; van Zwanenberg & Millstone, 2015); otherwise, they stay outside the public gaze.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…able to enroll and incorporate knowledges that are not regularly considered formal expertise, but stem from other origins such as crafts, traditions and practices. NGOs might be important providers of such knowledge, though trust in them as producers of reliable data is low (Han et al 2015;Pandey and Sharma 2017). 14 Thus, mobilizing discourse coalitions for inclusive policy-making requires that policy creates conditions for nurturing multiplicity of discourses, rather than works toward singular outcomes.…”
Section: Mobilizing Discourse Coalitions For Inclusive Policy-makingmentioning
confidence: 99%